Korean Wave Cultural Influence And Fan Entrepreneurship Behaviortowards Entrepreneurial Interests (Case Study On S1 Management Student, USU Faculty of Economics And Business) - Masturah, W Fildzah; Qaedi Hutagalung, Arif; Marhaini; Qamariah, Inneke (Journal Of Management Analytical and Solution (JoMAS), 2021)
The purpose of this study was to determine whether there is a positive and significant influence simultaneously   or   partially   on   Korean   Wave   culture   and   Fan   Entrepreneurship   behavior   on entrepreneurial interest in undergraduate (S1) students of Management, Faculty of Economics and Business, University of North Sumatra. The subjects of this study were undergraduate students (S1) in Management, Faculty of Economics and Business, University of North Sumatra from 2016 to 2019. The sample used was all 90 students. The dependent variable in this research is entrepreneurial interest (Y), while the independent variable includes Korean Wave culture (X1) and Fan Entrepreneurship behavior (X2). The data collection method used a questionnaire. The data analysis technique used descriptive statistical analysis, multiple regression analysis, F test, t test, and the coefficient of determination (R2). The results showed that Korean Wave culture and Fan Entrepreneurship behavior had a positive and significant effect on interest in entrepreneurship.  Korean Wave Culture and Entrepreneurship Fan Behavior have an effect of 29.4 percent simultaneously.